Factors Related to Mothers and the Prevalence of LBW - Ni Komang Erny Astiti; Ni Wayan Suarniti; Visti Delvina; Anna Maria Manullang; Inna Noor Inayati (CV. Get Press Indonesia, 2024)
Birth weight is a crucial indicator of infant health, influencing survival and future growth and mental development. In 2020, 40 mothers (7.19%) experienced preeclampsia during childbirth. Among mothers giving birth, 216 (39%) were primiparous, 300 (54%) multiparous, and 40 (7.19%) grand multiparous. This study aimed to identify maternal factors associated with the prevalence of low birth weight (LBW) in hospitals. Utilizing a case-control research design, this quantitative study employed an observational analytical method. The sample consisted of 60 controls and 30 cases of LBW infants, randomly selected from mothers who delivered between January and December. Data were analyzed using bivariate chi-square tests.The analysis revealed a significant relationship between preeclampsia and LBW incidence, with a prevalence ratio (PR) of 2.667 (95% CI = 1.591-4.470). To mitigate LBW rates, the Indonesian Ministry of Health has established health check-up guidelines for pregnant women. This initiative aims to enhance hospital programs addressing factors that contribute to LBW. Additionally, variables such as parity, anemia, and nutritional status did not show a significant correlation with LBW incidence.In conclusion, while preeclampsia was significantly linked to LBW, other maternal factors such as parity and nutritional status require further investigation to understand their potential impacts on birth weight outcomes effectively. The findings underscore the importance of comprehensive maternal healthcare to improve neonatal health outcomes and reduce the prevalence of LBW in future pregnancies.